Application of Kansei Engineering in the Development of Sambal Pecel Packaging Based on Consumer Preferences - Ika Riswi Aprilia; Novi Purnama Sari (Poltanesa, 2025)
Indonesia has a wealth of culinary archipelago, one of which is Sambal Pecel. Sambal Pecel is now not only sold in traditional markets, but also available in modern markets. Behind the popularity of Sambal Pecel, there are a number of problems that need to be considered regarding the design and functionality of the packaging used today. These problems include unattractive packaging design, lack of ease of storage, packaging that is difficult to open and cannot be closed again. Packaging redesign is needed to overcome these problems by considering the emotional aspects of consumers. This study aims to design the packaging of chili sauce pecel in accordance with consumer preferences using the Kansei Engineering (KE) method. The method is supported by Hierarchical Agglomerative Clustering (HAC) and K-Means methods in determining design concepts and Genetic Algorithm (GA) to determine packaging design elements. Based on the results of HAC analysis with average linkage calculation, 3 concept clusters were obtained, namely “Simple”, “Modern” and “Reusable”. The results through K-Means analysis obtained the selected design concept, namely the “Reusable” concept which represents consumer preferences. Analysis using GA, obtained packaging design elements include material “Polyethylene”, shape “Rectangle Tub”, lid “Snap On & Pull-Tab Lid”, features “Hanger Hole”, volume “Medium”, design “Modern”, color “Natural” and print type “Sticker”.